Analysis of named entity recognition and linking for tweets. Issue 2 (March 2015) - Derczynski, Leon; Maynard, Diana; Rizzo, Giuseppe; van Erp, Marieke; Gorrell, Genevieve; Troncy, Raphaël; Petrak, Johann; Bontcheva, Kalina
Highlights We analyse the named entity recognition and disambiguation performance on tweets. Multiple state-of-the-art systems are included. Commercial and academic systems suffer the same range of problems. Lack of context is a major problem, demanding new, custom NER & NEL approaches. A named entity linking corpus is released with the paper.